MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA MIND MAPPING BERBANTUAN APLIKASI EDRAW MINDMASTER PELAJARAN IPA DI KELAS V SDN SUKAMANAH 2 - Defita Khoerunisa, - (2022)
Defita Khoerunisa. 2022. Improving Student Learning Outcomes Throught Mind Mapping Media Assisted By The Edraw Mindmaster Applivation For Science Lesson In The Class V SDN Sukamanah 2. PGSD UPI Campus In Serang. Education is a very important part in realizing a nation's development and progress. In this 21st century era, all cannot be separated from the use of digital technology. Learning media will be used if the media is digital-based or interactive applications, one of which is mind mapping media which is assisted by the Edraw Mindmaster application, to further develop science learning outcomes. This research was conducted at SDN Sukamanah 2 Pandeglang. Researchers found problems in class V students and there were some students who scored less when learning science. So the solution is to use learning through mind mapping media which is assisted by the Edraw Mindmaster application. This type of research uses Classroom Action Research (CAR), to further develop science learning outcomes for fifth grade elementary school students with a total of 16 students. This research will be completed in 2 cycles, namely cycle I and cycle II, with 4 levels in each cycle, including planning, implementation, observation, and reflection. The instrument used by the researcher was the student activity sheet as a test, the student perception sheet and the teacher's perception. When conducting the research, the researcher saw that the students were cheerful when they got used to using mind mapping media which was assisted by the Edraw Mindmaster application. This can be seen from the percentage of student scores that increased significantly. When the learning media has not been used, the results of the science test questions with a passing percentage are only 18.75%. and after using mind mapping media, the results of the science learning test questions increased by a percentage of 81.25%. The test scores exceeded the expected target of 75% of the total number of students who were able to achieve the minimum completeness criteria (KKM).